Populism, Ideology and Voting in Europe. An Analysis of the Attitudinal and Partisan Maps of Italian, Spanish and French Public Opinions - Boscán, Guillermo; Llamazares, Iván; Wiesehomeier, Nina (CSIC Consejo Superior de Investigaciones Cientificas, 2018)
European party systems have witnessed the emergence of populist discursive elements among political parties with quite diverse ideological platforms. In this article we analyze the role and correlates of populist political attitudes in Spain,France,and Italy,three countries that present important differences in the nature of the parties articulating populist discourses. In the first place,we conduct factor analyses in order to explore the public opinion map of policy preferences and political attitudes in these three countries. These analyses reveal the presence of a clearly distinguishable dimension of populist attitudes in all these countries. In the second place,we examine the party system articulation of citizen preferences in the bi-dimensional spaces constituted by populist attitudes,left-right economic preferences,and preferences regarding immigration. Our analysis reveals strong associations between populist attitudes and left-right preferences at the party level,and the orthogonal relationship of populist attitudes and immigration preferences. Finally,our analysis of the socio-structural determinants of populist attitudes reveals the positive association of populist attitudes with lower income levels,less qualified occupations,and lower educational levels. © 2018 CSIC.
Actitudes populistas preferencias políticas y sistemas de partidos en españa francia e italia
Keywords: Europe; France; Italy; Political parties; Populist attitudes; Public Opinion; Spain; 59 Ciencia Política::5904 Instituciones políticas; ODS 10 - Reducción de las desigualdades